2021
DOI: 10.3390/jcm10102061
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolic Disease in Chronic Inflammatory Lung Diseases: Knowns and Unknowns

Abstract: Persistent inflammation within the respiratory tract underlies the pathogenesis of numerous chronic pulmonary diseases. There is evidence supporting that chronic lung diseases are associated with a higher risk of venous thromboembolism (VTE). However, the relationship between lung diseases and/or lung function with VTE is unclear. Understanding the role of chronic lung inflammation as a predisposing factor for VTE may help determine the optimal management and aid in the development of future preventative strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 86 publications
3
17
0
Order By: Relevance
“…Asthma specifi cally has been associated with increased risk of PE at an adjusted odds ratio of 1.4. 8 Percutaneous PFO closure is a treatment option for patients who remain symptomatic or hypoxemic despite optimal medical therapy but has not been shown to improve survival. 6,7 Further treatment was not indicated in the case patient.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma specifi cally has been associated with increased risk of PE at an adjusted odds ratio of 1.4. 8 Percutaneous PFO closure is a treatment option for patients who remain symptomatic or hypoxemic despite optimal medical therapy but has not been shown to improve survival. 6,7 Further treatment was not indicated in the case patient.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that asthma increases the risk for PE. In comparison with the non-asthmatic people, asthmatic patients of all age groups run an increased risk for PE, which is even more increased depending on the age and the severity of the respiratory disease [ 22 ]. Even in a stable phase, COPD is considered an independent risk factor for PE.…”
Section: Discussionmentioning
confidence: 99%
“…Even in a stable phase, COPD is considered an independent risk factor for PE. At the same time, a meta-analysis suggests that one out of four patients with a COPD exacerbation who need hospitalization may suffer from PE [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…and some specific genetic conditions (i.e., Factor V, protein C or protein S) account for less than one-fifth of the population attributable risk in the elderly [ 6 , 7 ], but most VTEs are provoked by weak risk factors or even no identifiable risk factors [ 1 , 8 ]. Published evidence indicates that poor lung function is related to increased atherothrombotic risk, with risk factors broadly similar to those for VTE [ 9 , 10 ]. Moreover, chronic lung diseases (e.g., chronic obstructive pulmonary disease (COPD) [ 9 , 11 ], asthma, emphysema, interstitial lung disease [ 12 ]) or postoperative lung cancer [ 13 ], characterized by varying degrees of impairment in different lung function parameters, are related to an increased risk of VTE [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Published evidence indicates that poor lung function is related to increased atherothrombotic risk, with risk factors broadly similar to those for VTE [ 9 , 10 ]. Moreover, chronic lung diseases (e.g., chronic obstructive pulmonary disease (COPD) [ 9 , 11 ], asthma, emphysema, interstitial lung disease [ 12 ]) or postoperative lung cancer [ 13 ], characterized by varying degrees of impairment in different lung function parameters, are related to an increased risk of VTE [ 10 ]. Another study pointed out that impaired lung function did not affect the VTE risk in cancer patients complicated with PE [ 14 ].…”
Section: Introductionmentioning
confidence: 99%